Differential impacts of fat and muscle mass on cardiovascular and non‐cardiovascular mortality in individuals with type 2 diabetes - Jie Guo; Yuxia Wei; Emerald G. Heiland; Anna Marseglia (Wiley, 2024)
Abstract Background The distribution of fat and muscle mass in different regions of the body can reflect different pathways to mortality in individuals with diabetes. Therefore, we investigated the associations between whole‐body and regional body fat and muscle mass with cardiovascular disease (CVD) and non‐CVD mortality in type 2 diabetes (T2D). Methods Within the National Health and Nutrition Examination Survey 1999-2006, 1417 adults aged ≥50 years with T2D were selected. Dual‐energy X‐ray absorptiometry was used to derive whole‐body, trunk, arm, and leg fat mass and muscle mass indices (FMI and MMI). Mortality data until 31 December 2019 were retrieved from the National Death Index. Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated from Cox proportional hazard models. Results A total of 1417 participants were included in this study (weighted mean age [standard error]: 63.7 [0.3] years; 50.5% female). Over a median follow‐up of 13.6 years, 797 deaths were recorded (371 CVD‐related and 426 non‐CVD deaths). Higher FMI in the arm was associated with increased risk of non‐CVD mortality (fourth quartile [Q4] vs. first quartile [Q1]: HR 1.82 [95% CI 1.13-2.94]), whereas higher FMI in the trunk or leg was not significantly associated with CVD or non‐CVD mortality. Conversely, higher arm MMI was associated with a lower risk of both CVD (Q4 vs. Q1: HR 0.51 [95% CI 0.33-0.81]) and non‐CVD (Q4 vs. Q1: HR 0.56 [95% CI 0.33-0.94]) mortality. There was a significant interaction between smoking status and arm FMI on non‐CVD mortality (P for interaction = 0.007). Higher arm FMI was associated with a higher risk of non‐CVD mortality among current or former smokers (Q4 vs. Q1: HR 2.67 [95% CI 1.46-4.88]) but not non‐smokers (Q4 vs. Q1: HR 0.85 [95% CI 0.49-1.47]). Conclusions Fat mass and muscle mass, especially in the arm, are differently associated with CVD and non‐CVD mortality in people with T2D. Our findings underscore the predictive value of body compositions in the arm in forecasting mortality among older adults with T2D.